Melanoma extracellular vesicles membrane coated nanoparticles as targeted delivery carriers for tumor and lungs - María Sancho-Albero; Alessandra Decio; Reha Akpinar; Ada De Luigi; Raffaella Giavazzi; Luigi M. Terracciano; Luisa De Cola (Materials Today Bio)
Targeting is the most challenging problem to solve for drug delivery systems. Despite the use of targeting units such as antibodies, peptides and proteins to increase their penetration in tumors the amount of therapeutics that reach the target is very small, even with the use of nanoparticles (NPs). Nature has solved the selectivity problem using a combination of proteins and lipids that are exposed on the cell membranes and are able to recognize specific tissues as demonstrated by cancer metastasis. Extracellular vesicles (EVs) have a similar ability in target only certain organs or to return to their original cells, showing home behavior. Here we report a strategy inspired by nature, using a combination of NPs and the targeting cell membranes of EVs. We implement the EV membranes, extracted by the EVs produced by melanoma B16-BL6 cells, as a coating of organosilica porous particles with the aim of targeting tumors and lung metastasis, while avoiding systemic effects and accumulation of the NPs in undesired organs. The tissue-specific fingerprint provided by the EVs-derived membranes from melanoma cells provides preferential uptake into the tumor and selective targeting of lungs. The ability of the EVs hybrid systems to behave as the natural EVs was demonstrated in vitro and in vivo in two different tumor models. As a proof of concept, the loading and release of doxorubicin, was investigated and its accumulation demonstrated in the expected tissues.